LncRNA growth arrest-special 5 polymorphisms and predisposition to cancer: A meta-analysis. Issue 4 (December 2020) - Cai, Hairong; Xu, Wenyan; Zhang, Xian
Aim: The lncRNA growth arrest-special 5 ( GAS5 ) is a critical tumor suppressor lncRNA, and its expression level has been found to be decreased in many types of cancers. So GAS5 polymorphisms are also likely to influence predisposition to many types of malignant diseases. Nevertheless, the relationships between GAS5 polymorphisms and cancer are still controversial. Thus, the authors designed this meta-analysis to get a more statistically reliable conclusion. Methods: The authors searched PubMed, Embase, and Web of Science for eligible studies. A total of 12 eligible studies involving 8693 cancer cases and 10, 805 controls were pooled and analyzed in this meta-analysis. Results: Among GAS5 polymorphisms, only GAS5 rs145204276 insertion/deletion polymorphism could be analyzed in a meta-analysis with regard to predisposition to cancer since no any other GAS5 polymorphisms were explored by at least two individual genetic association studies. All eligible studies were found to be of Asian origin. Although the overall pooled meta-analysis results did not show any significant associations between rs145204276 insertion/deletion polymorphism and a predisposition to cancer, rs145204276 insertion/deletion polymorphism was demonstrated to be significantly associated with a predisposition to gastric cancer (dominant comparison: P <0.0001; recessive comparison: P =0.005; over-dominant comparison: P =0.0003; over-dominant comparison: P <0.0001) in Asians in further subgroup analyses. Conclusions: This meta-analysis demonstrated that GAS5 rs145204276 insertion/deletion polymorphism was associated with a predisposition to gastric cancer in Asians. Nevertheless, considering that this positive finding was only based on three eligible studies from the same area, future studies with larger sample sizes in other populations are still warranted to test the robustness of our findings.